Spontaneous intracranial hypotension: searching for the CSF leak. Issue 4 (April 2022) - Dobrocky, Tomas; Nicholson, Patrick; Häni, Levin; Mordasini, Pasquale; Krings, Timo; Brinjikji, Waleed; Cutsforth-Gregory, Jeremy K; Schär, Ralph; Schankin, Christoph; Gralla, Jan; Pereira, Vitor M; Raabe, Andreas; et al.
Summary: Spontaneous intracranial hypotension is caused by loss of CSF at the level of the spine. The most frequent symptom of this disorder is orthostatic headache, with the headache worsening in the upright position and subsiding after lying down. Neuroimaging has a crucial role in diagnosing and monitoring spontaneous intracranial hypotension, because it provides objective (albeit often subtle) data despite the variable clinical syndromes and often normal lumbar puncture opening pressure associated with this disorder. Spine imaging aims to classify and localise the site of CSF leakage as either (1) a ventral dural leak, (2) a leaking spinal nerve root diverticulum, or (3) a direct CSF-venous fistula. Searching for a CSF leak can be very difficult; the entire spine must be scrutinised for a dural breach often the size of a pin. Precisely locating the site of CSF leakage is fundamental to successful treatment, which includes a targeted epidural patch and surgical closure when conservative measures do not provide long-term relief. Increased awareness of spontaneous intracranial hypotension among clinicians highlights the need for dedicated diagnostic and therapeutic guidelines.